Ascher syndrome: Review of literature and case report - B. A. Ramesh (Indian Journal of Plastic Surgery)
A 13 year old girl presented with aesthetic deformity of upper lip since birth. She also presented with eyelid swelling on and off for 11 months. She was diagnosed to be a rare case of Ascher syndrome. Ascher syndrome commonly presents with double lip and blepharochalasis, sometimes associated with goitre. The deformity of her double upper lip was corrected by appropriate surgery. Because her blepharochalasis is in active stage now, she is under periodic follow up for appropriate intervention. This article describes the management of the patient and brief overview of the syndrome. Ascher syndrome is often missed or misdiagnosed commonly.